Exosomes derived from osteogenic tumor activate osteoclast differentiation and concurrently inhibit osteogenesis by transferring COL1A1‐targeting miRNA‐92a‐1‐5p. Issue 3 (18th January 2021) - Yu, Lijuan; Sui, Bingdong; Fan, Weixiao; Lei, Lin; Zhou, Lei; Yang, Liu; Diao, Yanjun; Zhang, Yue; Li, Zhuo; Liu, Jiayun; Hao, Xiaoke
Abstract: In patients with prostate cancer (PCa), bone lesions appear osteoblastic in radiographs; however, pathological fractures frequently occur in PCa patients, and bone resorption is observed in all metastatic lesions under histopathologic assessment. The mechanisms that balance the activities of osteoblasts and osteoclasts in PCa patients remain unclear. We unexpectedly discovered that PCa exosomes are critical mediators in the regulation of bone homeostasis that results in osteoclastic lesions and thereby promotes tumor growth in bone. We evaluated how exosomes derived from osteoblastic, osteoclastic, and mixed PCa cell lines affect osteoblast and osteoclast differentiation, revealing that all three types of PCa exosomes promoted osteoclastogenesis in vitro and induced osteolysis in vivo. Mechanistically, microRNAs (miRNAs) delivered by PCa exosomes were found to play several key roles in bone homeostasis. Among the delivered miRNAs, miR‐92a‐1‐5p, the most abundant miRNA, downregulated type I collagen expression by directly targeting COL1A1, and thus promoting osteoclast differentiation and inhibiting osteoblastogenesis. Furthermore, PCa exosomes also markedly reduced type I collagen expression in vivo. Our findings not only offer a novel perspective on tumor bone metastasis, where—contrary to our initial hypothesis—exosomes derived from an osteoblastic tumor induce osteoclast differentiation, but also suggest potential therapeutic targets for PCa bone metastasis.